HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN SERVIS ATAS BOLA VOLI PADA SISWA ESKTRAKURIKULER DI SMPN 5 SINGINGI HILIR KECAMATAN SINGINGI HILIR - ASPERA, SIMAI; Juita., S.Pd, M.Pd, Ardiah; ', Drs. Ramadi., S.Pd., M.Kes AIFO (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is the lack of top serve ability being owned by the students of SMPN 5 Singingi Hilir. This problem is suspected because of the strength of the arm and shoulder muscles. To the researchers aim to prove the corelation between these variables. The method used is a corelational method. Population in this study were students of SMPN 5 Singingi Hilir District of Singingi Hilir who follow extracurricular activities totaled 25 students. The sampling technique used is total sampling so that the sample in this study there were 25 students. Data obtained from the test results pull up and test top serve volleyball. From the analysis, the correlation value can be seen that the value of r count is 0.619 with the value rtabel = 0.396, it means rcount = 0.619> rtabel = 0.396 and it can be said that there is a significant correlation strength of arms and shoulders muscle with the ability to top serve volleyball in students extracurricular activities at SMPN 5 Singingi Hilir District of Singingi Hilir. After the correlation number obtained, further testing the hypothesis by using t-test Significance formula. The calculation of the results t = 3.78, while ttabel with df = n-2 = 25-2 = 23 at 95% confidence level is 1.714. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that "there is a corealtion of arms and shoulders strength muscle with the ability to to serve volleyball in extracurricular student at SMPN 5 Singingi Hilir District of Singingi Hilir." Accepted.Keywords : Arm and Shoulders Strength Muscle, Top Serve, Volleyball2